HOW DO FIRMS OPEN UP THE FRONT-END OF SERVICE INNOVATION? A CASE STUDY OF IT-BASED SERVICE FIRMS IN THAILAND - BUNDIT THANASOPON; THANOS PAPADOPOULOS; RICHARD VIDGEN (My University, 2017)
This paper focusses on the openness in the front-end phase of service innovation and its impact on innovation success. The early stages of innovation are fuzzy and unstructured, thus often being called “fuzzy front-end” (FFE) by scholars. The FFE begins when an opportunity is considered worthy of further ideation, exploration, and assessment and ends when a firm decides to invest in — or terminate — an idea. Although openness has been identified as pivotal to innovation performance, little effort has been put into exploring its role in the early phase of innovation. By drawing on the data of a multiple case study in Thai online service firms, we are able to identify four key dimensions of FFE openness competence: prior related knowledge, top management support, the presence of workable prototype, and slack resource. Furthermore, we found three openness activities that often take place in the FFE phase of successful online service innovation, i.e., external search, inter-firm partnerships and customer experimentation. From a managerial perspective, our study provides useful insights to innovation managers aiming at enhancing front-end performance through openness.
Keywords: Openness to experience; Open Innovation; Service Innovation; Ideation; Product innovation; Innovation and Socioeconomic Development